2023
DOI: 10.1136/bmjopen-2022-066311
|View full text |Cite
|
Sign up to set email alerts
|

Burden experienced by informal caregivers of children with sickle cell disease (SCD): a qualitative exploratory study at Tamale Teaching Hospital, Ghana

Abstract: ObjectiveThis study sought to explore the burden experienced by informal caregivers in caring for their children with sickle cell disease (SCD).DesignA qualitative exploratory design was employed in the study using in-depth interviews.SettingThe study was conducted at the sickle cell clinic of the Tamale Teaching Hospital, Ghana.ParticipantsData were gathered from 15 purposively selected informal caregivers, whose children with SCD received care at the sickle cell clinic of the Tamale Teaching Hospital, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…This result is similar to findings from other studies where caregivers who have a child with SCD or a family history of SCD tend to more willingly accept the results. However, those families who have friends or community members with a child with severe SCD tend to have intense anxiety due to prior negative experiences with the disease [ 39 ]. In addition, parents who received results in a face-to-face setting as part of regular scheduled appointment reported that this method of disclosure was helpful [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to findings from other studies where caregivers who have a child with SCD or a family history of SCD tend to more willingly accept the results. However, those families who have friends or community members with a child with severe SCD tend to have intense anxiety due to prior negative experiences with the disease [ 39 ]. In addition, parents who received results in a face-to-face setting as part of regular scheduled appointment reported that this method of disclosure was helpful [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research findings indicate that as a child's illness advances, both the child and their caregivers undergo a decline in quality of life, leading to a notable deterioration in their physical, psychological, social, and economic welfare [ 18 ]. Caregivers of children with chronic illnesses, such as sickle cell disease and HIV, may experience significant impacts on their quality of life due to increased stress, financial strain, social isolation, and changes in routines [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%